Antagonistic activity of Rhodotorula mucilaginosa fungi isolated from the gastrointestinal tract of farm animals - Nikanova D.A.; Kolodina E.N.; Dovydenkova M.V.; Artemyeva O.A. (Ветеринария и кормление)
With the development of antibiotic resistance, the possibility of replacing anti-biotics with antimicrobial pigments for the treatment of infections caused by resistant pathogens is being considered. Actinobacteria, Rhodococci, and a number of fungi and yeasts, including Rhodotorula, have the greatest ability to produce pigments. A total of 28 strains of R. mucilaginosa isolated from the gastrointestinal tract of farm animals and poultry were selected for the study. The bacterial pathogens used in this study were E. coli 3912/41, S. aureus ATCC 25923, L. monocytogenes 766, S. flexneri 1a 8516, S. enterica serovar Typhimurium 79. After 24 hours of cultivation, the optical density (OD540) in the control test strain S. aureus ATCC 25923 was 1.145±0.023 units, while in the culture fluid of 16 strains of R. mucilaginosa OD540 did not exceed 1.0 units. The difference of OD540 in the culture of S. aureus cells in the crude extract of R. mucilaginosa yeast showed that 11 strains (2, 5, 6, 7, 10, 14, 17, 20, 23, and 25) inhibited and 4 strains (1, 8, 4, and 27) inhibited the growth of S. aureus (Pі0.001). The OD540 of the test strain S. flexneri 1a 8516 with the culture fluid of strains 11, 12, 24, 3, and 9 was lower (Pі0.001) than that of the control. OD540 of the culture fluid of eighteen strains (1, 10, 21, 16, 19, 15, 12, 25, 13, 6, 3, 11, 22, 2, 24, 27, 23 and 18) was lower than in the control with the test strain E. coli 3912/41. The minimum difference in optical density of the test strain S. enterica serovar Typhimurium 79 was observed in strains 1 and 6 and amounted to 0,278 and 0,252 units, compared to the control 0,286 units. The maximum growth inhibition of L. monocytogenes 766 was observed in the culture fluid of strains 10 and 14, so the difference in OD540 was 1,13 and 1,21 units (Pі0.001), and strains 5, 23 and 25 showed the same difference in OD540 (Pі0.05) of 0,135; 0,131 and 0,137 units.